Students' Perception Towards e-Learning During Covid-19 Pandemic in Malaysia: An Empirical Study - Binti Mohmad Sah, Farzana Adabiah; Che Him, Norziha; Rusiman, Mohd Saifullah (Enhanced Knowledge in Sciences and Technology, 2023)
Covid-19 has disrupted most of the industries in the world. Malaysia’s first case of Covid-19 has started in December 2019 shows that this pandemic has restructured the most of Malaysian’s lifestyle. However, accessibility issues and a lack of digital technologies in their local areas continue to have an impact on certain students. The objectives of this study are; 1) to investigate the implementations trend of e-learning before and after Covid-19; 2) to analyse the benefits of e-learning mode from student perspective during Covid-19 pandemic; and 3) to analyse the students’ perceptions of e-learning during Covid-19 lockdown period. A modified questionnaire after pilot test has spread to the respondent through WhatsApp and e-mail among Universiti Tun Hussein Onn Malaysia (UTHM) students. Around 109 of the 141 respondents, or 77.3%, are female, while 22.7% are male, with women constituting most respondents overall. Result for first objective shows that most of the students think e-learning achieved its aim during the Covid-19 pandemic and the second objective presents most students agreed that e-learning process is more comfortable in preparing answers for continuous assessment than face-to-face. Finally, the third objective shows that most of students interested with the idea behind the e-learning process during Covid-19. In conclusion, most of UTHM students agreed with the idea of the e-learning process during Covid-19 pandemic in Malaysia and most students at UTHM enjoyed the environment of online learning.